2020
DOI: 10.12659/msm.918751
|View full text |Cite
|
Sign up to set email alerts
|

Exonuclease 1 (Exo1) Participates in Mammalian Non-Homologous End Joining and Contributes to Drug Resistance in Ovarian Cancer

Abstract: Departmental sources Background: Exonuclease 1 (Exo1) participates in a variety of DNA damage repair, including mismatch repair, nucleotide excision repair, and homologous recombination. Genetic study in yeast indicates a role of Exo1 in non-homologous end joining (NHEJ), acting as a regulator for accuracy repairing DNA. This study aimed to investigate the effects of human Exo1 in NHEJ and drug resistance in ovarian cells. Material/Methods: Ectopic expression of Exo1 was carried out using pcDNA3.1-EXO1 plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…DNA topoisomerase 2-alpha ( TOP2A ), exodeoxyribonuclease 1 ( EXO1 ), serine/threonine-protein kinase Nek2 ( NEK2 ), baculoviral IAP repeat-containing protein 5 ( BIRC5 ), hyaluronan mediated motility receptor ( HMMR ), structural maintenance of chromosomes protein 4 ( SMC4 ), bloom syndrome protein ( BLM ), casein kinase I isoform epsilon ( CSNK1E ), cytoskeleton-associated protein 5 ( CKAP5 ), and inner centromere protein ( INCENP ) were identified as the hub genes based on the degrees of nodes which were more than 10 ( Figure 2 a) [ 11 ]. TOP2A , EXO1 , NEK2 , BIRC5 , SMC4 , BLM , CSNK1E , CKAP5 , and INCENP were related to DNA replication and cell division, and HMMR was related to cell motility [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The detailed functions of the hub genes are described in the discussion section and Supplementary Table S3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA topoisomerase 2-alpha ( TOP2A ), exodeoxyribonuclease 1 ( EXO1 ), serine/threonine-protein kinase Nek2 ( NEK2 ), baculoviral IAP repeat-containing protein 5 ( BIRC5 ), hyaluronan mediated motility receptor ( HMMR ), structural maintenance of chromosomes protein 4 ( SMC4 ), bloom syndrome protein ( BLM ), casein kinase I isoform epsilon ( CSNK1E ), cytoskeleton-associated protein 5 ( CKAP5 ), and inner centromere protein ( INCENP ) were identified as the hub genes based on the degrees of nodes which were more than 10 ( Figure 2 a) [ 11 ]. TOP2A , EXO1 , NEK2 , BIRC5 , SMC4 , BLM , CSNK1E , CKAP5 , and INCENP were related to DNA replication and cell division, and HMMR was related to cell motility [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The detailed functions of the hub genes are described in the discussion section and Supplementary Table S3 .…”
Section: Resultsmentioning
confidence: 99%
“…EXO1 genes which are related to mismatch repairing were recognized as the new cancer driver genes in a recent study, which are closely related to m6A RNA methylation-related genes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“… 40 Moreover, cell cycle-associated proteins have been shown to modulate the effectiveness of radiation and chemotherapy. 41 , 42 Several SNPs of EXO1 have been confirmed to be associated with radiotherapy or chemotherapy resistance, such as radiotherapy resistance in glioblastoma cell lines, 38 chemotherapy resistance in ovarian cancer, 43 and resistance to cisplatin treatment in NSCLC patients. 44 And in our study, we found that EXO1 was highly expressed in TP53-mutant group compared with TP53-wild-type group in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Centromere protein I (CENPI) is a structural component of the kinetochore, required for timely progression through G2 phase, mitosis, and chromosome stability [48,49]. Exonuclease I (EXO1) contributes to the regulation of the cell cycle checkpoints, the maintenance of the replication fork, DNA repair, and genomic instability [50,51]. Kinetochore scaffold 1 (KNL1) is essential in spindle assembly checkpoints, chromosome segregation, and kinetochore-microtubule attachments [52,53].…”
Section: Discussionmentioning
confidence: 99%